2021
DOI: 10.1007/s42161-021-00752-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Erwinia amylovora isolates detected in the wild walnut-fruit forest of South Kyrgyzstan

Abstract: Erwinia amylovora, the causal agent of fire blight, was first reported in Kyrgyz orchards in 2008 and, within a few years, the disease has spread throughout most of the northern part of the country. As fire blight expanded and penetrated new areas, it also reached the unique ecosystem constituted by the Arslonbob wild walnut-fruit forests in South Kyrgyzstan. Here, we present the results of field surveys in the forests and in the nearby orchards and gardens of the Jalal-Abad region during the 2019 season. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…This severe disease, which affects plants belonging to the family Rosaceae, is thought to have originated in North America, moved to New Zealand, where it was first detected in 1910, and arrived in the United Kingdom in 1958, before sequentially spreading to virtually every country of continental Europe and in the Mediterranean area during the second part of the twentieth century (Bonn and van der Zwet 2000). In the first two decades of the new millennium, fire blight has progressively moved eastward reaching Russia (Jock et al 2013), the Caucasus region (Gaganidze et al 2018(Gaganidze et al , 2021, Central Asia (Djaimurzina et al 2014;Doolotkeldieva et al 2021) and South Korea (Park et al 2017). Phylogeographic studies based on the diversity of CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) regions have revealed that the extreme genetic homogeneity of the pathogen outside its center of origin is largely due to a bottleneck effect, resulting from a restricted number of dissemination events of so-called CRISPR group I strains radiating from the East Coast of the United States (Rezzonico et al 2011;McGhee and Sundin 2012) or possibly even introduced from New Zealand (Bühlmann 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This severe disease, which affects plants belonging to the family Rosaceae, is thought to have originated in North America, moved to New Zealand, where it was first detected in 1910, and arrived in the United Kingdom in 1958, before sequentially spreading to virtually every country of continental Europe and in the Mediterranean area during the second part of the twentieth century (Bonn and van der Zwet 2000). In the first two decades of the new millennium, fire blight has progressively moved eastward reaching Russia (Jock et al 2013), the Caucasus region (Gaganidze et al 2018(Gaganidze et al , 2021, Central Asia (Djaimurzina et al 2014;Doolotkeldieva et al 2021) and South Korea (Park et al 2017). Phylogeographic studies based on the diversity of CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) regions have revealed that the extreme genetic homogeneity of the pathogen outside its center of origin is largely due to a bottleneck effect, resulting from a restricted number of dissemination events of so-called CRISPR group I strains radiating from the East Coast of the United States (Rezzonico et al 2011;McGhee and Sundin 2012) or possibly even introduced from New Zealand (Bühlmann 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Losses in the provision of ecosystem services are then analogous to crop losses. However, this aspect has rarely been reported, and most studies have concentrated on the role of wild plants as reservoirs or alternate hosts of pathogens infecting crop or cultivated plants (Mugerwa et al, 2021, Doolotkeldieva et al 2021, Pak et al, 2021, Regassa et al, 2021Electronic Supporting Information, S5).…”
Section: Climate Change Yield and Ecosystem Servicesmentioning
confidence: 99%
“…The bacterial cultures used in this work were isolated from diseased organs of apple and pear trees grown in orchards and forestry farms in northern and southern Kyrgyzstan. They were genetically identified, and their degree of pathogenicity was determined [37,38].…”
Section: Effects Of Nps On Plant Pathogensmentioning
confidence: 99%